Electroluminescence of Light- Emitting Organic Semiconductor/ Europium Oxide Nanoparticle Hybrid Junction - Mohammed, Hussein Riyadh; Ibrahim, Omar A. (Iraqi Journal of Science, 2020)
A hybrid nanoparticles light emitting diode (NPs-LED) was fabricated as layers of ITO/TPD:PMMA/ Eu2O3 / Alq3 / Al, by phase segregation method using spin coating technique. The NPs-LED hybrid device emitted light and consisted of three layers in a definite order placed on the transparent conducting oxide as an ITO substrate; the first layer was made of (N, N’-bis (3-methylphenyl) -N, N’-bis (phenyl) benzidine) (TPD) and polymethyl methacrylate (PMMA) polymers combined together. The second layer consisted of Europium (III) oxide (Eu2O3), while the third layer was Alq3, one of the most frequently-used electron transport layers. The electroluminescence (EL) of NPs-LED was studied with different bias voltages (20, 25 and 30V) at room temperature. Depending on the CIE 1931 color spaces, X the white light was generated at 30V and the green light at 20V. This was achieved by benefitting from the transition between deep levels in the energy gap of Eu2O3 NPs (surface state ) and magnetic dipole transition for Eu+ (5D0-3and5L6 to 7F0-6). The Current â€“ Voltage (I-V) characteristics demonstrated that the current varies with voltage and that the knee voltage value is 5 V. The EL spectrum showed a broad band emission, with a range of 350 - 700 nm. Finally, the correlated color temperature (CCT) was found to be about 7100 to 11500k.